Ruthenium nanoclusters modified by zinc species towards enhanced electrochemical hydrogen evolution reaction - Zhang, Hefeng; Qi, Shengliang; Zhu, Kaixin; Zong, Xu (Frontiers in Chemistry, 2023)
Ruthenium (Ru) has been considered a promising electrocatalyst for electrochemical hydrogen evolution reaction (HER) while its performance is limited due to the problems of particle aggregation and competitive adsorption of the reaction intermediates. Herein, we reported the synthesis of a zinc (Zn) modified Ru nanocluster electrocatalyst anchored on multiwalled carbon nanotubes (Ru-Zn/MWCNTs). The Ru-Zn catalysts were found to be highly dispersed on the MWCNTs substrate. Moreover, the Ru-Zn/MWCNTs exhibited low overpotentials of 26 and 119 mV for achieving current intensities of 10 and 100 mA cm−2 under alkaline conditions, respectively, surpassing Ru/MWCNTs with the same Ru loading and the commercial 5 wt% Pt/C (47 and 270 mV). Moreover, the Ru-Zn/MWCNTs showed greatly enhanced stability compared to Ru/MWCNTs with no significant decay after 10,000 cycles of CV sweeps and long-term operation for 90 h. The incorporation of Zn species was found to modify the electronic structure of the Ru active species and thus modulate the adsorption energy of the Had and OHad intermediates, which could be the main reason for the enhanced HER performance. This study provides a strategy to develop efficient and stable electrocatalysts towards the clean energy conversion field.